Avaliação do perfil químico e atividades biológicas de Myrcíaria Strigipes O. Berg (Myrtaceae) - Faitanin, Rafael Destefani (2016)
Brazil is the owner of the largest and richest genetic diversity of plant species, however, most of them don’t have chemical-biologial studies. Myrciaria strigipes O. Berg (Myrtaceae) is a native species known popularly as "cambucá da praia" and "cabeludinha da praia" and it’s used in traditional medicine for cramps, edema and abdominal pain. The aim of this study was to evaluate the chemical profile, the toxicity and the antimicrobial, antioxidant, thrombolytic activities and α-amylase, α- glucosidase and tyrosinase enzymes inhibition activities of M. strigipes. The chemical profile was characterized from phytochemical screening, High Performance Liquid Chromatography analysis and the fractionation/purification techniques. The toxicity was determined against larvae of Artemia salina Leach. and the antimicrobial activity against Staphylococcus aureus, Escherichia coli and Candida albicans. The antioxidant activity was measured using the synthetic radicals DPPH and ABTS. The in vitro thrombolytic activity was evaluated through the extracts capacity to cause lysis in human blood clot. The inhibitory activities of α-amylase, α-glucosidase and tyrosinase enzymes were determined using in vitro spectrophotometric methods. Preliminary phytochemical analysis of ethanolic extracts of leaves (EEF) and branches (EEG) indicated the presence of flavonoids, coumarins, alkaloids, saponins, tannins, triterpenes, steroids and anthraquinones, yet this was only found in the EEF. They were isolated and/or identified of the EEF five compounds of terpenes class, four pentacyclic triterpenes (friedelin, 28-hydroxyfriedelin, glutinol and ursolic acid) and a tetracyclic steroid (β-sitosterol), and three phenolic compounds (isoquercitrin, hyperoside and ellagic acid). The EEF showed a little toxicity (LD50 = 648.17 µg/mL) and only the EEG showed antimicrobial activity, inhibiting the growth of S. aureus. The EEF and EEG showed antioxidant capacity and promising inhibitory activity on α-glucosidase, EC50 of 40,66 e 18,52 µg/mL, respectively, while the positive control showed EC50 of 37,30 µg/mL. This study reported, for the first time, chemical aspects and biological activities of M. strigipes species, and the results demonstrate the need for more studies to further chemical knowledge and understanding about the mechanism(s) and substance(s) responsible for activities shown by this species.